Analisis kedisiplinan belajar pada peserta didik kelas iv sekolah dasar - Ramadhani, Fadhiilah Suci; Poerwanti, Jenny Indrastoeti Siti; Sularmi, Sularmi (Universitas Sebelas Maret, 2022)
This research was conducted to describe the results of student learning discipline analysis so that it is expected to motivate students to pay attention to learning discipline. This research is qualitative research. The subjects of this study were fourth-grade students, fourth-grade teachers, and the student's parents. Data collection techniques in this study used a questionnaire, observation, and interviews. Indicators of learning discipline are discipline to school rules, discipline to follow learning, discipline to do assignments, and discipline to study at home. The results showed that the highest percentage was 61% of the indicators of discipline in school discipline in the medium category, 68% of the indicators of discipline following learning at school were in the medium category, 68% of the indicators of discipline in doing assignments were in the medium category, and 79% of the indicators of home study discipline are in the medium category. The average percentage obtained from the four indicators shows the medium category. Based on these percentages, it can be concluded that the learning discipline of fourth-grade students at SD Negeri Karangasem IV is in the medium category. Student learning discipline is influenced by interests, motivations, friends, school, teachers, and parents.